2021
DOI: 10.1155/2021/6727843
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Profile and Five-Year Trend Analysis of Malaria Prevalence in Maygaba Health Center, Welkait District, Northwest Ethiopia

Abstract: Background. Malaria is a serious public health problem of most developing countries, including Ethiopia. The burden of malaria is severely affecting the economy and lives of people, particularly among the productive ages of rural society. Thus, this study was targeted to analyze the past five-year retrospective malaria data among the rural setting of Maygaba town, Welkait district, northwest Ethiopia. Methods. The study was done on 36,219 outpatients attending for malaria diagnosis during January 2015 to 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The observation that the malaria burden was higher in male febrile patients compared to females in the study area corroborates reports by Tigu et al, (22) and Yimer et al, (23) in Ethiopia and a similar study conducted in South West Region of Cameroon (24). This finding also tallieswith previous studies conducted in the central Africa sub-region (25,26) and has also been reported in other studies (27)(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 92%
“…The observation that the malaria burden was higher in male febrile patients compared to females in the study area corroborates reports by Tigu et al, (22) and Yimer et al, (23) in Ethiopia and a similar study conducted in South West Region of Cameroon (24). This finding also tallieswith previous studies conducted in the central Africa sub-region (25,26) and has also been reported in other studies (27)(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 92%
“…Malaria transmission peaks in most Ethiopian regions from September to December following a heavy summer rainy season, with lower transmission lasting from April to May following a short rainy season [5]. Furthermore, the prevalence and incidence of malaria vary according to sociodemographic risk factors such as age and gender [6]. The country is prone to cyclic epidemics every 5 to 8 years due to unstable transmission patterns and environmental changes [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prevalence and incidence of malaria vary according to sociodemographic risk factors such as age and gender [6]. The country is prone to cyclic epidemics every 5 to 8 years due to unstable transmission patterns and environmental changes [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, evidence shows that higher positivity rate ranged up to 41.53% was reported from the studies conducted in Welkait District, three zones (Central, North and West Gonder) of Amhara region, Gambella region and South Omo zone [ 8 , 9 , 16 , 23 ]. The existence of such variation may be explained by differences in ecology, climatic, and sociocultural conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Ethiopia is a high malaria burden country with 60% of the population living in high transmission areas (the total population of the country being 102.8 million in 2020) [ 5 , 6 ]. However, the distribution and transmission of malaria varies across the country depending on rainfall patterns, altitude, and ecological and climate variations [ 7 , 8 ]. Evidences showed that, in Ethiopia, malaria accounts for loss of 30% of the overall disability adjusted life years (DALYs) [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%